Electronic and thermoelectric properties of polyaniline organic semiconductor and electrical characterization of Al/PANI MIS diode - Yakuphanoğlu, Fahrettin; Senkal, B. F. (Amer Chemical Soc, 2007)
The electrical conductivity, thermoelectric power, and metal-insulator-semiconductor diode properties of polyaniline prepared in ionic liquid (PANI) have been investigated. The electrical conductivity of the polyaniline increases exponentially with increasing temperature. The electrical conductivity value at 28 degrees C is 0.21 S/cm. The Seebeck coefficient of the PANI decreases with increasing temperature. The electrical conductivity and thermoelectric power results suggest that the PANI is a p-type semiconductor polymer. The Al/PANI Schottky diode was fabricated and is a metal-insulator-semiconductor type device. The ideality factor n and barrier height phi(b) values of the diode at 298 K were found to be 2.78 and 0.85 eV, respectively. The barrier inhomogeneities are a very important explanation of the higher values of the ideality factor. The Gaussian distribution function was suggested for describing barrier height inhomogeneities. The standard deviation of the barrier height distribution sigma(o) indicates the presence of the interface inhomogeneities. The phi(B) value obtained from C-V measurement is higher than that of the phi(B) value obtained I-V measurements.
Keywords: Ionic Liquids; Capacitance-Voltage; Polypyrrole Films; Barrier Height; Schottky Diode; Molten-Salts; Polymerization; Electrochemistry; Aluminum; Emulsion